The new leader's 100-day action plan : take charge, build your team, and deliver better results faster - Bradt, George B.; Check, Jayme A.; Lawler, John A. (Business professional collection, 2022)
"This revision of the popular guide for leaders in new roles has been updated with new chapters, including sample 100-day action plans as well as: How to build relationships and lead new remote colleagues How to get up to speed and lead your new organization's digital initiatives How to build relationships and lead in a new organization for Diversity, Equity, and Inclusion Whether you are joining a new organization from the outside, getting promoted from within, leading a turnaround or transformation, or merging teams following an acquisition, The New Leader's 100-Day Action Plan will help you take charge, build your team, set direction, and deliver better results faster than anyone thought possible. A practical playbook, this book is complete with the tools, action plans, timelines and key milestones you need to reach along the way to accelerate your own and your team's success in your first 100 days and beyond"--